Conceptualising national identity in late twelfth-century chansons de geste composed in French - Goodwin, E (2022)
This thesis challenges previous perceptions about national identity by dissolving the usual boundaries in which literary scholars and critics operate. It contends that the emergence and dynamic reconfiguration of national identity permeates a group of concepts which combine and reformulate themselves within intricate systems of lexical patterns entwined in the text, rather than being confined to a single concept.